Kepemilikan Rumah Hunian Oleh Orang Asing Diatas Hak Milik - I Nengah Suriata (Visi Sosial Humaniora, 2024)
The need for residential housing for foreigners who reside is a basic right that should be considered. Foreigners who have competencies in the field of tourism, managers, and other expertise for the Indonesian state are very realistic because the knowledge of foreigners' work skills for progress is mostly owned by foreigners. Indonesia as a country that will lead to progress is in dire need of knowledge and skills in various fields of technology, management and increasing resources both human and natural resources. The research method is carried out with the type of normative legal research method, with the source of primary legal material Government Regulation of the Republic of Indonesia Number 103 of 2015 concerning Ownership of Residential Houses or Occupancy by Foreigners Residing in Indonesia, and other laws and regulations related to the issues discussed. While secondary legal materials are library books, journal articles on line journal system, scientific papers, and reviews in the mass media and others. The results of the study indicate that there is conformity between the Republic of Indonesia Government Regulation Number 103 and the Republic of Indonesia Government Regulation in Article 4 letter a and number 1 of Number 10 of 1996 concerning Cultivation Rights, Building Rights and Land Rights Article 39 letter e and land objects Article 40 letter c, as well as the Republic of Indonesia Government Regulation Number 18 of 2021 concerning Land Management Rights, Land Rights, Flat Housing Units and Land Registration Article 49 paragraph (1).